Konseling Kelompok Dengan Teknik Relaksasi Kesadaran Indera Untuk Meningkatkan Kontrol Diri Terhadap Emosi Marah Pada Remaja di Panti Sosial Bina Remaja Palangka Raya - Ayu Putri Ningsih; Diplan Diplan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine the effectiveness of group counselling with sensory awareness relaxation techniques to improve self-control of angry emotions in adolescents at the Palangka Raya Youth Development Institution. The population in this study were all adolescents in the Palangka Raya Community Development Board of Social Institutions, which amounted to 30 teenagers consisting of 26 men and four women. Sampling is determined by purposive sampling technique. Data collection techniques used are observation, documentation and scale. The data analysis technique used in this study is the t-test (paired sample t-test). From the analysis of t-test results (paired sample t-test), it is known that t count is -10, 380 with a probability value or sig. (2-tailed) of 0, 000 <0, 05, because of the sig value. (2-tailed) of 0, 000 less than 0.05, it can be concluded that